The Khmer Witch Project: demonizing the Khmer by khmerizing a demon - Baumann, Benjamin (DORISEA working paper, 2015)
This paper outlines an anthropological reading of Thai ghost films and their uncanny protagonists as a dialectic synthesizing ethnographic material with film analysis in an attempt to operationalize the premises of the 'ontological' and 'spectral turns'. The paper is the first systematic study of Phi Krasue—one of Thailand's most iconic uncanny beings—and its cinematic and vernacular ghostly images. It grew out of an attempt to make sense of local Khmer-speaking interlocutors' acceptance and reproduction of an idiosyncratic origin myth that locates the origin of Phi Krasue in Angkorian Khmer culture. Based on Mary Douglas' and Julia Kristeva's theories the paper identifies abjection and its essential ambiguity as the logical principle structuring imaginations of Phi Krasue in vernacular and cinematic contexts. I argue that the reading of a ghost film's social message depends on spectators' embodiment of vernacular ghostlore and thus on an implicit knowledge of the cultural semantics Thailand's phi manifest. However, this paper offers not only a structural explanation for the self-evidence of Phi Krasue’s origin in Angkorian Khmer culture, but also for the Khmer-magic link as the most important socio-cultural stereotype characterizing the category 'Khmer' in Thailand's contemporary popular culture. Finally, the paper identifies 'filthiness' as the social idiom used to explicate abjection as the logical principle structuring processes of 'self-formation' in contemporary Thailand.